Enhanced and selective adsorption of Hg2+ to a trace level using trithiocyanuric acid-functionalized corn bract. (January 2019) - Lin, Guo; Wang, Shixing; Zhang, Libo; Hu, Tu; Cheng, Song; Fu, Likang; Xiong, Chao
Abstract: A novel trithiocyanuric acid-modified corn bract (TCA-CCB) was prepared, and its removal properties for Hg 2+ were investigated. TCA-CCB showed a remarkable absorbability for Hg 2+ in mixed ion solutions. Adsorption kinetics experiments indicated that the removal of Hg 2+ on TCA-CCB was quick, with a removal rate of 99.07% within 5 min. In addition, the removal rate of Hg 2+ exceeded 98% over all pH conditions. The adsorption process can be best described by pseudo-second-order kinetic and Hill isotherm models. The saturated adsorption capacity of TCA-CCB for Hg 2+ was 390 mg/g. The TCA-CCB could efficiently adsorb Hg 2+ from the simulated wastewater and reduce the Hg 2+ concentration from 10 ppm to 12.35 ppb, which was lower than the greatest allowable value of 50 ppb and satisfied the emission standards required by the Chinese government. Moreover, the removal rate of Hg 2+ was beyond 99% after three cycles. The results of the zeta potential and X-ray photoelectron spectroscopy (XPS) implied that the chelation and ion exchange between amino/thiol groups and Hg 2+ played a significant role in the improvement of the adsorption properties. The corn bract modified by trithiocyanuric acid exhibits apparent advantages in the removal of Hg 2+ from ppm to ppb due to its high selectivity, adsorption capacity and stability. Graphical abstract: Image 1 Highlights: A novel trithiocyanuric acid functionalized corn bract (TCA-CCB) was synthesized. The TCA-CCB showed high selectivity and efficiency for trace Hg 2+ removal. The TCA-CCB can reduce the Hg 2+ concentration as low as 12.35 ppb. The removal rate of Hg 2+ was higher than 99% after three cycles.